Autonomy Related Actions within Peer Group Spaces and Resilient Identity among Mid Adolescents in Mbengwi Sub Division in Cameroon - Muki , Asangha Ngufor (Journal of Innovation in Education and Social Research, 2024)
This study investigated “Autonomy Related Actions within Peer Group Spaces and Resilient Identity among Mid Adolescents” in Mbengwi Sub Division, Northwest Region of Cameroon. Some mid adolescents in Mbengwi are faced with adverse conditions such as, poverty, low socioeconomic status, and loss of parent or parents that put them at risk of developing emotional and behavioural problems. Despite all these adversities faced by these adolescents, most of them still cope and develop successfully. Their ability to overcome such adversities often results from the interplay of individual characteristics, the characteristics of the family, as well as those of the physical, social environment and the peer group. Hence, this study investigated whether autonomy related actions within peer group spaces fosters the development of resilient identity among mid adolescents. A concurrent mixed method design of both the descriptive survey and ethnographic design were used to conduct this study. A sample of 300 mid adolescents and 10 parents were chosen for this study using purposive and incidental sampling techniques. Both descriptive and inferential statistics were used to analyse collected data. Based on the above, it was realised that the predictor variables “autonomy related actions within peer spaces among mid adolescents” (X2=79.221; df =5; P<0.001), significantly foster the development of resilient identity (social competence, sense of purpose and problem solving) among mid adolescents. It should be noted that, the autonomy related actions within peer spaces among mid adolescents that foster resilient identity include; taking and acting on personal decisions confidently without any social validation, self-governing themselves, their behaviours and their activities, managing and spending their money responsibly, maintaining mature emotional connections with adults and peers and strongly believing that anything they want to do, they should do it well and successfully. At the end of the study, recommendations were pointed out for the empowerment of adolescent peer groups.